Synthesis of 2-Methoxy-3H-Azepine Derived Compounds Through the Thermal Reaction between Alkylnitrobenzene and Tributylphosphine - Siti Mariyah Ulfa; Hideki Okamoto; Kyosuke Satake (Natural B, Journal of Health and Environmental Sciences, 2015)
Although photolysis of phenyazide has been widely reported to give 3H-azepine, the thermal deoxygenation reaction of alkylnitrobenzene derived similar products hitherto unexplored. Novel synthesis of 2-methoxy-3H-azepine derivatives was carried out using alkylnitrobenzene with tributylphosphine (Bu3P) reacted at 150°C for 24 hours in the presence of methanol. Reaction of m-nitrobenzene with the above methods gave two isomers of 3H-azepine, namely, 2-methoxy-6-methyl-3H-azepine and 2-methoxy-4-methyl-3H-azepine in 61%. Reaction of 2,3-dimethylnitrobenzene with Bu3P afforded the three isomers, that is, 2-methoxy-6,7-dimethyl-3H-azepine; 2-methoxy-3,4-dimethyl-3H-azepine and 7-methoxy-5,6-dimethyl-4H-azepine. Reaction of 3,5-dimethylnitrobenzene gave the sole product of 2-methoxy-4,6-dimethyl-3H-azepine in 42%. In contrast, reaction of 2,6-dimethylnitrobenzene didn’t give any product because the steric effect of methyl groups attached on C2 and C6. Structure elucidation of all novel products have confirmed by HETCOR.